Civil war in Myanmar: A further escalation of violence looms on the horizon - Felix Heiduk (Stiftung Wissenschaft und Politik (SWP), 2021)
Military installations have been attacked in various towns in Myanmar's interior over the past few days. Among other things, military airfields that the air force had used to attack ethnic minority rebel bases in the east and north of the country were fired upon. So far, no one has claimed responsibility for the attacks, but it can be assumed that they are connected to the newly formed alliance between the former democratic government and ethnic minorities. In view of this development, the violent conflicts in Myanmar threaten to spread from the border regions to the entire country, including large urban centres. If the violence were indeed to escalate in the coming weeks, Myanmar would be further destabilised politically, economically, and socially.
Keywords: 320